As bruxas da modernidade: os discursos presentes em Malleus Maleficarum e suas influências na luta feminista - FERREIRA, Suzi André (2021)
This research presents as its central theme the permanence of the discourses conveyed in the book Malleus Maleficarum and its influences on modern discourses. In this perspective, the present study aims to investigate how the characteristics associated with women in the Middle Ages echo in the discourses of contemporary society. Thus, we sought to analyze how discourses reproduced between the V and XV centuries spread in society, perpetuating themselves in the popular imagination and, today, becoming part of the ideology accepted by a particular class. To conduct this research, a qualitative theoretical-methodological analysis was conducted, anchored in the literature review, collecting data that were selected excerpts from the book Malleus Maleficarum, as well as selected from the social network twitter 50 tweets that present content with discourses that are related to excerpts from the medieval book. Given these analyzes, it was possible to raise reflections about the processes that lead to the recognition of the witches of modernity that are configured in women who fight against the stereotypes and societal paradigms that insist on undermining the female figure in contemporary society.